2021
DOI: 10.1111/ipd.12928
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of water fluoridation in an upper‐middle‐income country: A systematic review and meta‐analysis

Abstract: Aim To summarize the information on the effectiveness of community water fluoridation (CWF) on the reduction of dental caries in the context of the wide use of fluoridated toothpaste in Brazil. Design A systematic review was conducted regarding the effect of CWF based on studies with Brazilian population groups using the following electronic databases: MEDLINE/PubMed, LILACS, SciELO, and SCOPUS. The literature search was conducted up to August 2019. Studies that compared caries experience in at least two areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…On the other hand, the findings in the present study suggest that it is important to prevent dental caries in students before they enter university. Dentists and healthcare providers should continue to provide and also expand public health methodology for dental caries prevention, including supervised regular use of fluoride mouth rinses [29] and water fluoridation [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the findings in the present study suggest that it is important to prevent dental caries in students before they enter university. Dentists and healthcare providers should continue to provide and also expand public health methodology for dental caries prevention, including supervised regular use of fluoride mouth rinses [29] and water fluoridation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be plausible to investigate the reason why fluoridation provisions did not reach more municipalities, given that the cost of the measure was reduced when a water treatment and supply structure existed and that the efficiency of the service was not affected [ 76 , 77 ]. Moreover, it has proven to be effective even with the widespread use of fluoridated toothpaste [ 78 ]. A study based on the theory of street-level bureaucracy investigated small towns in a high-coverage region of the country.…”
Section: Discussionmentioning
confidence: 99%
“…In permanent dentition, water fluoridation can also reduce caries prevalence. However, the systematic review and meta-analysis indicated that water fluoridation had a higher impact on caries prevention in the primary dentition 8 . The lack of water fluoridation is associated with the increase in severity and prevalence of dental caries 7 .…”
Section: Introductionmentioning
confidence: 97%